Identifying gene expression profiles associated with neurogenesis and inflammation in the human subependymal zone from development through aging - Mainá Bitar; Christin Weissleder; Hayley F. North; Misaki S. Clearwater; Oressia Zalucki; Glenda M. Halliday; Maree J. Webster; Michael Piper; Cynthia Shannon Weickert; Guy Barry (Scientific Reports, 2022)
Abstract The generation of new neurons within the mammalian forebrain continues throughout life within two main neurogenic niches, the subgranular zone (SGZ) of the hippocampal dentate gyrus, and the subependymal zone (SEZ) lining the lateral ventricles. Though the SEZ is the largest neurogenic niche in the adult human forebrain, our understanding of the mechanisms regulating neurogenesis from development through aging within this region remains limited. This is especially pertinent given that neurogenesis declines dramatically over the postnatal lifespan. Here, we performed transcriptomic profiling on the SEZ from human post-mortem tissue from eight different life-stages ranging from neonates (average age ~ 2 months old) to aged adults (average age ~ 86 years old). We identified transcripts with concomitant profiles across these decades of life and focused on three of the most distinct profiles, namely (1) genes whose expression declined sharply after birth, (2) genes whose expression increased steadily with age, and (3) genes whose expression increased sharply in old age in the SEZ. Critically, these profiles identified neuroinflammation as becoming more prevalent with advancing age within the SEZ and occurring with time courses, one gradual (starting in mid-life) and one sharper (starting in old age).